WOMENPRENEUR MINDSET HOME INDUSTRY “ANEKA CEMILAN ASYIFAH ” IN THE DISTRICT OF RENGAT - Meilya Karya Putri (JURNAL MANAJEMEN DAN BISNIS, 2022)
This study aims to determine how to develop the mindset of women entrepreneurs. This research is qualitative descriptive field research, because it wants to get a description of the Womenpreneur Mindset in the Home Industry "Aneka Cemilan Asyifah" Rengat District, Indragiri Hulu Regency. The data collection method used is Observation, Interview, Documentation. The Credibility Test used is Extended Observation, Increasing Perseverance, Triangulation, Reference Material, Member Check. The results of this study are 5 (five) Mindset elements, namely Passion, Self Leadership Habits, Creativity Habits, Improvisation Habits, and Self-Efficacy owned by Womenpreneur "Aneka Cemilan Asyifah". The Home Industry entrepreneur "Aneka Cemilan Asyifah" shows that the entrepreneur has the passion to be an entrepreneur according to his hobbies in the culinary business, and sees a business opportunity. Even though there are obstacles, they are still looking for solutions to be able to survive in the culinary business that the entrepreneur is living. Home Industry Entrepreneur "Aneka Cemilan Asyifah" can direct and lead his members or employees, the desire to stay in the culinary business since 2015 is carried out by implementing various strategies assisted by his members. The strategy is to keep the business running for a long time, apart from doing creative promotions through the use of social media, a creativity mindset is also done by creating innovative products that are different from the products that have existed in Rengat. The improvised habit mindset is by producing products that have never existed before using quality materials and improving service to customers by delivering the ordered products to the customer's place. The fifth mindset is also evidenced by the statement submitted by the entrepreneur which shows that being an entrepreneur is of course a boss who can manage his own business without being regulated by others and is caused by having a hobby of cooking, so he wants to become a Womenpreneur or female entrepreneur in the culinary field.